Efficacy of Nigella sativa seeds oil in patients with Behcet's disease: a double-blind randomized controlled trial - Hadiseh Kavandi; Mehrzad Hajialilo; Alireza Khabbazi (Mashhad University of Medical Sciences, 2018)
Objective: Nigella sativa (NS) is a herbal medicine with anti-inflammatory and anti-oxidant functions. This study was designed to evaluate the effect of oral administration of NS seeds oil on the treatment of Behcet's disease (BD). Materials and methods:In this double-blind randomized controlled study, 130 patients with BD were screened and 71 patients with BD were randomly allocated to the treatment (n=37) and control (n=34) groups. Finally, 32 and 30 patients in the treatment and control groups, respectively, completed the study.The study protocol was registered in the Iranian Registry of Clinical Trials (IRCT) with registration No. IRCT201511086975N5. Treatment and control groups received soft gels containing 1000 mg NS oil or 1000 mg placebo per day for 12 months, respectively. Disease activity using the Iranian Behcet's disease dynamic activity measure (IBDDAM), total inflammatory activity index (TIAI) and Behcet's disease current activity form (BDCAF) were evaluated in all patients before initiation of the trial and every 2 months, for 12 months. Results: Disease activity decreased in the study groups; difference between the two groups was not significant. No serious adverse events were seen in the treatment and control groups. Conclusion: NS oil at the dose of 1000 mg/day is not effective in controlling BD activity.